Body trajectory optimisation of walking gait for a quadruped robot - Minghuan Zhang; Yaguang Zhu; Ao Cao; Qibin Wei; Qiong Liu (IET Cyber-systems and Robotics, 2023)
Abstract To ensure that the robot can follow the planned trajectory, smooth switching between swinging legs and a smooth transition of motion process is realised. The previous motion planning work is analysed, and a method for improving the optimisation objective function and constraint conditions is proposed to eliminate the sudden change of acceleration and reduce the peak value of acceleration change. This method eliminates the impact phenomenon in the motor drive process and reduces the motor drive energy consumption, thus ensuring the smooth and consistent movement of the robot. The results show that the improved optimisation method has a better motion effect than the previous approach in terms of centre of mass motion speed, trajectory fitting and body posture change, and realises more robust motion of quadruped robots in a senseless state.